Hepatic Adenosine Triphosphate Reduction Through the Short‐Chain Fatty Acids–Peroxisome Proliferator‐Activated Receptor γ–Uncoupling Protein 2 Axis Alleviates Immune‐Mediated Acute Hepatitis in Inulin‐Supplemented Mice. Issue 9 (2nd June 2021) - Yamaguchi, Akihiro; Teratani, Toshiaki; Chu, Po‐sung; Suzuki, Takahiro; Taniki, Nobuhito; Mikami, Yohei; Shiba, Shunsuke; Morikawa, Rei; Amiya, Takeru; Aoki, Ryo; Kanai, Takanori; Nakamoto, Nobuhiro
Abstract : How liver tolerance is disrupted in immune‐mediated liver injury is currently unclear. There is also insufficient information available regarding susceptibility, precipitation, escalation, and perpetuation of autoimmune hepatitis. To explore how dietary fiber influences hepatic damage, we applied the concanavalin A (ConA)‐induced acute immune‐mediated liver injury model in mice fed a diet supplemented with 6.8% inulin, a water‐soluble fermentable fiber. Twelve hours after ConA administration, inulin‐supplemented diet‐fed mice demonstrated significantly alleviated hepatic damage histologically and serologically, with down‐regulation of hepatic interferon‐γ and tumor necrosis factor and reduced myeloperoxidase (MPO)‐producing neutrophil infiltration. Preconditioning with an inulin‐supplemented diet for 2 weeks significantly reduced hepatic adenosine triphosphate (ATP) content; suramin, a purinergic P2 receptor antagonist, abolished the protective effect. Of note, the portal plasma derived from mice fed the inulin‐supplemented diet significantly alleviated ConA‐induced immune‐mediated liver injury. Mechanistically, increased portal short‐chain fatty acid (SCFA) levels, such as those of acetate and butyrate, by inulin supplementation leads to up‐regulation of hepatic γ‐type peroxisome proliferator‐activated receptor ( Pparg ) and uncoupling protein 2 ( Ucp2 ), which uncouples mitochondrial ATP synthesis downstream of PPARγ. Pparg down‐regulating small interfering RNA cancelled the protective effect of inulin supplementation against MPO‐producing neutrophil infiltration and the subsequent immune‐mediated liver injury, suggesting that the SCFA–PPARγ–UCP2 axis plays a key role in the protective effect by inulin supplementation. Moreover, significant changes in the gut microbiota, including increased operational taxonomic units in genera Akkermansia and Allobaculum, also characterized the protective effect of the inulin‐supplemented diet. Conclusion : There is a possible unraveled etiopathophysiological link between the maintenance of liver tolerance and dietary fiber. The SCFA–PPARγ–UCP2 axis may provide therapeutic targets for immune‐mediated liver injury in the future.